2020
DOI: 10.1101/2020.03.10.985739
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-chain lanthanide luminescence biosensors for cell-based imaging and screening of protein-protein interactions

Abstract: Research tools that enable imaging or analysis of protein-protein interactions (PPIs) directly within living cells provide unique and valuable biological insights and can also aid drug discovery efforts. Here, we present lanthanide-based, Förster resonance energy transfer (lanthanide-based FRET, or LRET) biosensors for time-gated luminescence (TGL) imaging or multiwell plate analysis of PPIs.Polypeptide chains comprised of an alpha helical linker flanked by a Tb(III) complex, GFP and two binding domains exhibi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Using FRET microscopy and an engineered cell line that stably expressed a Ypet/mCerulean sensor with a 20 nm ER/K linker, we observed robust Rac1 activation near protruding edges of stimulated cells. These results, along with our earlier studies, 22 demonstrate that FRET or LRET biosensors with ER/K linkers are a robust platform for engineering sensitive single cell imaging studies or higher-throughput cell-based assays of protein function in live cells.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…Using FRET microscopy and an engineered cell line that stably expressed a Ypet/mCerulean sensor with a 20 nm ER/K linker, we observed robust Rac1 activation near protruding edges of stimulated cells. These results, along with our earlier studies, 22 demonstrate that FRET or LRET biosensors with ER/K linkers are a robust platform for engineering sensitive single cell imaging studies or higher-throughput cell-based assays of protein function in live cells.…”
Section: Introductionsupporting
confidence: 75%
“…We previously showed that biosensors which incorporate Tb(III) complexes as LRET donors, GFP as LRET acceptors and ER/K linkers can be used to craft cell-based TGL assays of protein-protein interactions that exhibit exceptional sensitivity and dynamic range. 22 Inclusion of an eDHFR domain permits self-assembly with TMP-Tb(III) complex conjugates inside live cells or in cell lysates. TGL detection of LRET offers high signal-to-background ratios that derive from the ms-scale emission decay times of Tb(III) luminescence and Tb(III)-to-GFP sensitized emission.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation